PERAN UNITED NATIONS EDUCATIONAL, SCIENTIFIC AND CULTURAL ORGANIZATION (UNESCO) DALAM KONSERVASI SITUS WARISAN DUNIA DI KOTA SAWAHLUNTO: OMBILIN COAL MINING HERITAGE OF SAWAHLUNTO - Hasrul Muhammad; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Ombilin Coal Mining Heritage of Sawahlunto was approved as a world cultural heritage by UNESCO in 2019. OCMHS itself has extraordinary universal value, namely a combination of European industrial technology at the end of the 19th century and local wisdom. OCMHS itself has 12 components and 24 attributes as world heritage objects and intangibles. OCMHS, assessed to have very high authenticity. The property as a whole bears a high degree of authenticity as a prime example of the surviving heritage of large-scale coal mining in the late 19th and early 20th centuries in Southeast Asia. In this study, the author utilizes the theory of International Organizations. The author also employs a qualitative research method with a descriptive model. In this research, the data used consists of both primary and secondary data. Data collection techniques used include field studies and literature reviews. In this study the authors found research results, namely the role of UNESCO in OCMHS conservation carried out by vendors or third parties, namely the South East Asia Museum Service (SEAMS). SEAMS as a consultant conducted a form of survey activity, namely the Baseline Survey of Interpretation Strategy of the World Heritage Site of Ombilin Coal Mining Heritage of Sawahlunto. The results of this survey are a collection of OCMHS interpretation data. This collection of interpretations will be concluded and SEAMS will make several recommendations for future conservation. Keywords: UNESCO, World Cultural Heritage, Conservation, OCMHS, SEAMS